The epithelial-mesenchymal transition phenotype is associated with the frequency of tumor spread through air spaces (STAS) and a High risk of recurrence after resection of lung carcinoma. (March 2021) - Ikeda, Toshihiro; Kadota, Kyuichi; Yoshida, Chihiro; Ishikawa, Ryou; Go, Tetsuhiko; Haba, Reiji; Yokomise, Hiroyasu
Highlights: We analyzed EMT phenotypes in patients with therapy-naive lung carcinoma. STAS was less frequently observed in tumors with epithelial phenotype. EMT phenotype was independent prognostic factor of recurrence in STAS patients. Abstract: Objectives: The prognostic value of spread through air spaces (STAS) in lung carcinoma has been validated in independent cohorts. Epithelial-mesenchymal transition (EMT) is a biological process that promotes the migration and invasiveness of tumor cells. To investigate the role of the EMT phenotype in the occurrence of STAS, we analyzed patients with therapy-naive lung adenocarcinoma and squamous cell carcinoma undergoing lobectomy (n = 635). Materials and Methods: STAS was defined by the presence of tumor cells within air spaces in the lung parenchyma beyond the edge of the main tumor. The expression of E-cadherin, vimentin, and ®-catenin was evaluated by immunohistochemistry using tissue microarray. Tumors were classified into three EMT phenotypes (epithelial, intermediate, and mesenchymal). Recurrence-free probability and overall survival were analyzed using the log-rank test and the Cox proportional hazards model. Results: STAS was less frequently observed in tumors with epithelial phenotype than in those with non-epithelial phenotype (p = 0.034), and more frequent in patients with nuclear β-catenin-positive tumors (p < 0.001). The EMT phenotype was an independent prognostic factor of recurrence (mesenchymal vs. epithelial: hazard ratio [HR] = 2.27, p = 0.014; mesenchymal vs. intermediate: HR = 2.13, p = 0.019). Conclusion: We have demonstrated that in patients with resected lung carcinoma, STAS was less frequent in tumors with an epithelial phenotype than in those with non-epithelial phenotype, and that the nuclear translocation of β-catenin was associated with a higher rate of STAS. The mesenchymal state was an independent predictor of high risk of recurrence in patients with STAS.